The Differences Between the Application of the Think Pair Share (TPS) Cooperative Learning Model and the Conventional Model to Student Physics Learning Outcomes - La Ode Asmin; Mujerimin Mujerimin; La Isa; Halmuniati Halmuniati; Zainuddin Zainuddin (Universitas Islam Negeri (UIN) Mataram, 2023)
The purpose of this study was to compare the application of the think pair share (TPS) learning method and conventional methods to student learning outcomes in physics learning. The type of research used is quasi-experimental (Quasy Experimental Design). The subjects in this study were two classes, namely 24 X MIPA 1 students as an experimental class using the Think Pair Share (TPS) learning method and 24 X MIPA 2 students as a control class using conventional methods. The sampling technique used purposive sampling. Data collection techniques using documentation, tests, and observations. The data analysis technique used in this study was the Independent Sample Test (t-test) with a significance level of 5%. Before the data were analyzed, a prerequisite test for normality analysis was carried out. The results showed that there were differences in the learning outcomes of students who were taught using the TPS method with conventional methods in physics subjects. Where the average post-test score for the experimental class was 72.45, higher than the control class, which was 51.54. These results indicate that student learning outcomes in the experimental class experienced a significant increase compared to the control class. The results of calculating the gain score for the experimental class obtained an average pre-test of 54.04 and a post-test of 72.45 so a Gain of 0.40 was obtained in the moderate category. Whereas in the control class, the average pre-test was 49.87 and the post-test was 51.54 so a gain of 0.03 was obtained in the low category. This shows that learning using the TPS method is better than using conventional methods.